Motivasi Mahasiswa Terhadap Penggunaan Penuntun Praktikum Fisiologi Hewan Berbasis Inkuiri Terbimbing - Diana Susanti; Rina Widiana; Ramadhan Sumarmin; Silvi Susanti (BIOEDUSCIENCE, 2021)
Guidance on guided animal inquiry based practicology has been developed with valid, practical and effective results. The guide developed is guided inquiry-oriented which can help students find their own knowledge when practicum activities are carried out. Guides developed are also in accordance with the correct guiding component. The purpose of this study is to see the results of student motivation in using guided inquiry-based physiology practicum guides. This research is a development study using the 4D model, the data is processed using a percentage formula. The results of data processing show that the motivation of students who use practicum guides get a percentage of 80.2% (highly motivated) and those who do not use practicum guides is 84.14% (highly motivated) It can be concluded that students are highly motivated towards the use of practicum guided animal physiology guides